2018
DOI: 10.1039/c8cp04940h
|View full text |Cite
|
Sign up to set email alerts
|

Surface oxygen-containing defects of graphene nanosheets with tunable nonlinear optical absorption and refraction

Abstract: Nonlinear optical response of graphene is weakened whether surface oxygen-containing content is too large or too small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Recently, Zhu et al studied the effect of synergy between CdS and graphene on nonlinear optical properties [19]. Zhu et al researched the nonlinear optical properties of oxygen-containing defects in CdS/graphene [20,21]. Yin et al invented a nonlinear optical imaging technique by nonlinear optical symmetry [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhu et al studied the effect of synergy between CdS and graphene on nonlinear optical properties [19]. Zhu et al researched the nonlinear optical properties of oxygen-containing defects in CdS/graphene [20,21]. Yin et al invented a nonlinear optical imaging technique by nonlinear optical symmetry [22].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows the UV-Vis absorption peak position of the sample. The absorption peak of GO was at 228.96 nm, which might be mainly derived from the π-π* transition of C-C and C=C in sp 2 hybridization [ 30 ]. For ZrO 2 /RGO nanocomposites, with the increase of ZrO 2 concentration, the absorption peaks were located at 262.79 nm, 264.16 nm, 266.07 nm, and 275.15 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of ZrO 2 concentration, the nonlinear refraction firstly decreased and then increased, which indicated that the combination of ZrO 2 and RGO had a synergistic effect on the nonlinearity. The normalized CA/OA Z-scan experimental data were fitted by the following equation [ 30 ]: where x = z/z 0 , was the on-axis phase shift at the focus, defined as , k = 2 /λ was the wave vector, λ was the laser wavelength, , was the nonlinear refractive index coefficient in m 2 /W, represented the difference between the normalized transmitted peaks and valleys of the open/closed Z-scan trace, S was the fluence of the aperture. Then, the nonlinear refraction index was calculated by .…”
Section: Resultsmentioning
confidence: 99%
“…The peaks located at 1251 and 956 cm −1 are ascribed to the stretching vibrations of the epoxy groups (C‒O‒C) [33,34,35]. The peaks at 1147 and 1070 cm −1 are attributed to C‒O vibrational mode for alkoxy groups [36,37,38]. The small peak at 1766 cm −1 corresponds to the C=O stretching vibration mode [39].…”
Section: Resultsmentioning
confidence: 99%